Scientific and theoretical bases of efficiency of farm facilities: Dasar ilmiah dan teoritis dari efisiensi fasilitas pertanian - Barno Shukhratovna Akbarova (Universitas Muhammadiyah Sidoarjo, 2019)
The article is devoted to the peculiarities of agriculture in Uzbekistan and the problems of agrarian reforms and institutional transformations, the search for new organizational forms and management methods capable of ensuring the effective use of land, water, material and financial resources, as well as prospects for the development of the agricultural sector of the republic.